Genome-wide analysis of the TPX2 family proteins in Eucalyptus grandis. (December 2016) - Du, Pingzhou; Kumar, Manoj; Yao, Yuan; Xie, Qiaoli; Wang, Jinyan; Zhang, Baolong; Gan, Siming; Wang, Yuqi; Wu, Ai-Min
Abstract Background The Xklp2 (TPX2) proteins belong to the microtubule-associated (MAP) family of proteins. All members of the family contain the conserved TPX2 motif, which can interact with microtubules, regulate microtubule dynamics or assist with different microtubule functions, for example, maintenance of cell morphology or regulation of cell growth and development. However, the role of members of the TPX family have not been studied in the model tree speciesEucalyptus to date. Here, we report the identification of the members of the TPX2 family inEucalyptus grandis (Eg) and analyse the expression patterns and functions of these genes. Results In present study, a comprehensive analysis of the plant TPX2 family proteins was performed. Phylogenetic analyses indicated that the genes can be classified into 6 distinct subfamilies. A genome-wide survey identified 12 members of theTPX2 family in the sequenced genome ofEucalyptus grandis . The basic genetic properties of the TPX2 family in Eucalyptus were analysed. Our results suggest that the TPX2 family proteins within different sub-groups are relatively conserved but there are important differences between groups. Quantitative real-time PCR (qRT-PCR) was performed to confirm the expression levels of the genes in different tissues. The results showed that in the whole plant, the levels ofEgWDL5 transcript are the highest, followed by those ofEgWDL4 . Compared with other tissues, the level of theEgMAP20 transcript is the highest in the root. Over-expression ofEgMAP20 in Arabidopsis resulted in organ twisting. The cotyledon petioles showed left-handed twisting while the hypocotyl epidermal cells produced right-handed helical twisting. Finally, EgMAP20, EgWDL3 and EgWDL3L were all able to decorate microtubules. Conclusions Plant TPX2 family proteins were systematically analysed using bioinformatics methods. There are 12 TPX2 family proteins inEucalyptus . We have performed an initial characterization of the functions of several members of theTPX2 family. We found that the gene products are localized to the microtubule cytoskeleton. Our results lay the foundation for future efforts to reveal the biological significance of TPX2 family proteins inEucalyptus .